Biocontrol efficacy of cajeput oil against Anopheles stephensi L. mosquito and its effect on non-target species - Vivekanandhan, Perumal; Alahmadi, Tahani Awad; Ansari, Mohammad Javed; Subala, S. P. (Frontiers in Physiology, 2024)
Chemical insecticides are effective at controlling mosquito populations, but their excessive use can pollute the environment and harm non-target organisms. Mosquitoes can also develop resistance to these chemicals over time, which makes long-term mosquito control efforts challenging. In this study, we assessed the phytochemical, biochemical, and insecticidal properties of the chemical constituents of cajeput oil. Results show that Melaleuca cajuputi essential oil may exhibit mosquito larvicidal properties against Anopheles stephensi larvae (second-fourth instar) at 24 hours post-treatment. At 24 hours post-exposure, the essential oil resulted in a significant decrease in detoxifying enzymes. All of these findings indicate that cajeput oil infects An. stephensi larvae directly affect the immune system, leading to decreased immune function. Cajeput oil significantly affects the second, third, and fourth instar larvae of An. stephensi, according to the bioassay results. Cajeput oil does not induce toxicity in non-target Eudrilus eugeniae earthworm species, as indicated by a histological study of earthworms. Phytochemical screening and GC-MS analysis of the essential oil revealed the presence of several major phytochemicals that contribute to mosquito larvicidal activity. The importance of cajeput oil as an effective candidate for biological control of the malarial vector An. stephensi is supported by this study.